ANALYSES OF JUNIOR HIGH SCHOOL SCIENCE COMPETENCIES IN KTSP AND INTEGRATED-REVISION OF 2013 CURRICULUM: REVIEWED FROM THE POTENTIAL OF DISASTER MITIGATION EDUCATION FOR THE SHAPING OF A DISASTER RESPONSE CHARACTER - Rangga Sena Aji Hamisesa; Fitri Handayani Nataliya; Reno Nurdiyanto; Pujianto Pujianto (Journal of Science Education Research, 2018)
This study aims to analyze the science competencies in the JHS (Junior High Schools) which is integrated to disaster mitigation education (earthquake, tsunami, and volcano) in the School-Based Curriculum (KTSP) and the revised 2013 Curriculum in shaping a disaster response character. This study focuses on operational competencies that are potential to be integrated with disaster mitigation education, especially geological disasters. This was a library research analyzing any issues (problems) based on supporting literature reviewed. The data were collected through documentation, observation, and recorded findings that support to the research focus. As many as 40 science teachers and all documents of the implementation of the KTSP and revised-2013 Curriculum were involved in this study. Then the data were analyzed using a coding technique according to the components of the research focus and described qualitatively. The results of the study show that the number of science-competencies which have the potential to be integrated with disaster mitigation education is considered low compared to the whole of Science competencies that students must achieve. 0.48 % of science-competencies in JHS are potential to be integrated with disaster mitigation education. These competencies are 0.72 % in grade VII, 0.25% in grade VIII, and 0.5% in grade IX. These findings indicate that the contents of the curriculum have not been considered as a means of instilling the natural disaster response character